Space, time, and presence in video consultations: an interview study in Danish general practice - Frida Greek Kofod; Anne-Marie Søndergaard Christensen; Elisabeth Assing Hvidt; Anne Beiter Arreskov; Ann Dorrit Guassora (BMC Primary Care)
Abstract Background The purpose of this interview study was to explore patients’ and general practitioners’ (GPs’) experiences of space, time, and presence in video consultation in general practice in Denmark. Methods The study included six GPs and seven patients from the Copenhagen area, with different experience of video consultations. The data consisted of semi-structured interviews with all participants including recordings from their video consultations. The transcribed interviews were analyzed by Interpretative Phenomenological Analysis (IPA). The theoretical analysis was inspired by philosopher K.E. Løgstrup’s writings about time, space, presence and sensation. Results Both the patients and the GPs experienced a lack, or a different form, of presence in video consultations, comparing it to face-to-face consultations. Patients felt more secure in their own homes and the GPs found some of them to be more relaxed during the video consultation than in the face-to-face consultation taking place in the surgery. However, the consultation felt more superficial, with the GPs and patients experiencing an alteration in their sensory access to one another. The video consultation was also perceived as purpose-driven and action-oriented. Both patients and GPs felt that time was saved. According to K.E. Løgstrup, our experience is always composed of spatiality and temporality; the space is where we sense one another and experience duration, while time is the awareness of change and action. The theoretical analysis points to the experience of presence as spatial and, owing to the changed space in video consultations, the experience of presence and time is changed. Conclusion and Implications The balance between space and time is altered in the video consultation. GPs and patients lack certain sensory impressions, owing to the changed spatiality. The changed spatiality, sensation and experiences of presence lead the participants to eliminate the expendable elements to make the consultation more efficient. Video consultations allow some issues to be handled quickly, but the option for physical consultations still needs to be available, as we believe we now can argue that the physical consultation room has importance for the experience of presence and time.